Decomposing International Trade in Commercial Services. Issue 3 (August 2021) - Roelfsema, Hein; Findlay, Christopher; Ye, Xianjia
To delve deeper into the rise of trade in commercial services as the most important determinant of the recent increase in digital trade, this article offers a decomposition of international service trade using the latest release of the Inter-Country Input–Output (ICIO) tables. The analysis decomposes international service trade into a split between (a) direct services exports and services embodied in goods, (b) advanced economies and the major emerging markets, and (c) the major commercial services industries. We show that overall direct service exports have become more important relative to services embodied in goods, especially in advanced economies (the 'cross-border' effect). Further, we show that for emerging markets, the rise of the exports of services comes from the increase in volume of export of goods, which embed services and not because of an increased share of services embodied in the domestic value of exported goods (the 'embodied volume' effect). Finally, we show that the increase in services trade can be attributed to the increase in traded information technology (IT) services and not so much to that in financial and business services that are increasingly traded digitally across borders (the 'plain vanilla digitalisation' effect). JEL Codes: F14, F15, G20